Studying and enhancing professional learning community for school effectiveness in Iceland - Anna Kristín Sigur_ardottir (Universidad Autónoma de Madrid, 2015)
Improving school towards more effectiveness in terms of students learning is a complex task, influenced by contextual and cultural factors. Characteristics of effective schools are relatively well known in the literature, but the relationship of those is still controversial. Many questions are still unanswered on effective ways of improving schools. Even though Hopkins (2001) claims that "we know enough about the theory and practice of educational change to successfully improve schools" (16), educationalists all over the world are dealing with this task with different success.